(untitled) (Eurasian Medical Research Periodical, 2025)
This article focuses on the pathophysiological mechanisms of uteroplacental blood flow impairment in preeclampsia and its role in the development of fetal hypoxia. The study included pregnant women diagnosed with preeclampsia, in whom uteroplacental hemodynamic parameters were evaluated using Doppler ultrasound. The analysis demonstrated that impaired spiral artery remodeling, endothelial dysfunction, and placental ischemia play a crucial role in restricting oxygen and nutrient delivery to the fetus. Understanding these mechanisms may contribute to early diagnosis and the development of effective preventive strategies aimed at reducing perinatal morbidity and mortality